About a concept of creating a social network users information aggregation and data processing system - L. V. Rudikova; O. R. Myslivec (Системный анализ и прикладная информатика, 2019)
The development of a general concept and implementation of a data-storage and analysis system for practice oriented data, one of the subsystems of which is an analytical system for the accumulation and analysis of data from users of social networks, is topical. The development of a general concept and implementation of a data-storage and analysis system for practice oriented data, one of the subsystems of which is an analytical system for the accumulation and analysis of data from users of social networks, is topical. Data that users leave about themselves in social networks can be useful in solving various tasks. The proposed article describes the subject area associated with the collection and storage of data from users of social networks. Proceeding from the subject area, the general architecture of the universal data collection and storage system is proposed, which is based on the client-server architecture. For the server side of the system, a fragment of the data model is provided, which is associated with the accumulation of data from external sources. The framework of the system architecture is described. The developed universal system is based on the information technology of data warehousing, and it has the following aspects: an expandable complex subject area, the integration of stored data that come from various sources, the invariance of stored data in time with mandatory labels, relatively high data stability, the search for necessary trade-off in data redundancy, modularity of individual system units, fl and extensibility of the architecture, high security requirements vulnerable data.The proposed system organizes the process of collecting data and filling the database from external sources. To do this, the system has a module for collecting and converting information from third-party Internet sources and sending them to the database. The system is intended for various users interested in analyzing data of users of social networks.